Identification and classification of objects in images obtained by UAV and orbital base imaging equipmenttion - A. A. Doudkin; V. V. Ganchenko; A. V. Inyutin; E. E. Marushko (Системный анализ и прикладная информатика)
To identify and classify objects on images obtained using UAV imaging and orbital-based imaging, a neural network classification model based on the use of an autoencoder and built on the architecture of an ensemble of multilayer perceptrons is proposed. Additionally, at the stage of highlighting informative features, is added a color information, which is based on the per-channel histograms and is invariant to the scale and rotations of the image. The model is implemented using the Keras library. The use of the proposed model for classification into four classes: “Fire”, “Smoke”, “Vegetation” and “Buildings”, allows to achieve a classification accuracy above 99%.